2009
DOI: 10.4161/epi.4.3.8753
|View full text |Cite
|
Sign up to set email alerts
|

Role of histone acetylation in the activity-dependent regulation of sulfiredoxin and sestrin 2

Abstract: Peroxiredoxins are neuroprotective antioxidant enzymes that reduce hydroperoxides and protect neurons against oxidative stress. However, they can be inactivated through hyperoxidation of their active site cysteine, an event that can take place in the brain in response to oxidative insults such as stroke and also normal aging. Synaptic activity promotes the reduction of hyperoxidized peroxiredoxins in neurons, and induces the expression of sulfiredoxin (Srxn1) and sestrin 2 (Sesn2) which have been reported to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…Emerging evidence indicates that acetylation and deacetylation of histones can profoundly influence various functions of neurons, including cell death in response to stress (Mattson, 2003;Rouaux et al, 2003;Soriano et al, 2009). First, we examined whether exposure to the neurotoxic pesticide dieldrin induces acetylation of histones in dopaminergic neuronal cell models.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence indicates that acetylation and deacetylation of histones can profoundly influence various functions of neurons, including cell death in response to stress (Mattson, 2003;Rouaux et al, 2003;Soriano et al, 2009). First, we examined whether exposure to the neurotoxic pesticide dieldrin induces acetylation of histones in dopaminergic neuronal cell models.…”
Section: Resultsmentioning
confidence: 99%
“…Most strikingly, recent studies using disease models show that the balance in histone acetylation/ deacetylation can be a determining factor in mediating cell survival and cell death (Marchion and Mü nster, 2007;Soriano et al, 2009). For example, an HDAC inhibitor, which induces histone hyperacetylation, could cause death in cancer cells (Aron et al, 2003;Condorelli et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Securin deficiency causes genomic instability and might regulate Sesn2 via p53 activation. Sesn2 transcriptional activity is also regulated by the mechanisms involved acetylation/deacetylation of histones, which can be controlled by oxidative stress and other stimuli [130]. In accordance, treatment with the histone deacetylase inhibitor trichostatin A (TSA) induces Sesn2 expression in neurons [130].…”
Section: Identification and Characterization Of Sestrinsmentioning
confidence: 99%
“…However, it has been demonstrated that hyperoxidized PRX can be reversed to the catalytically active form, by sestrin 2 and sulfiredoxin (SRX) which utilizes ATP. [8][9][10] Interestingly, hyperoxidized PRXs retain some reducing capacities 6 and the newly formed structures have been proposed to signify a change in PRXs role as antioxidants to molecular chaperones during oxidative stress. 6,11,12 Modulation of H 2 O 2 , a second messenger, enables PRXs to serve diverse roles in immunity response, apoptosis, cell proliferation, cell differentiation, and cell signaling.…”
Section: Physiological Functions Of Prxsmentioning
confidence: 99%
“…As previously mentioned, hyperoxidation of PRXs can be reversed by sestrin 2, an enzyme that is epigenetically regulated, whereby histone acetylation by HDACi trichostatin A (TSA) treatment can enhance sestrin 2 transcription and thus contribute to increased PRX activity. 10 miRNAs miRNAs belong to a class of small non-coding RNAs (22 nucleotides) that regulate expression of genes implicated in crucial cellular processes, such as proliferation, apoptosis, development, and differentiation. [67][68][69] These miRNAs cleave target mRNAs or inhibit protein translation based on the complementarity to their targets.…”
Section: Regulation Of Prxs Via Epigenetic Mechanismsmentioning
confidence: 99%